(Non) Linear Regression Modeling - Pavel Čížek (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
We will study causal relationships of a known form between random variables. Given a model, we distinguish one or more dependent (endogenous) variables Y = (Y1, . . . , Yl), l ∈ N, which are explained by a model, and independent (exogenous, explanatory) variables X = (X1, . . . ,Xp), p ∈ N, which explain or predict the dependent variables by means of the model. Such relationships and models are commonly referred to as regression models.
Keywords: 330